Reconstructing the man-made Yellow River flood of Kaifeng City in 1642 AD using documentary sources. (December 2019) - Wu, Pengfei; Liu, Dexin; Ma, Jianhua; Gu, Lei; Tong, Jiahuan
Abstract: The Yellow River flood of September 1642 AD was one of the most extreme events inflicted on Kaifeng city which also had ramifications across the wider Yellow River region. Using all the available and predominantly non-instrumental data, this paper presents a geographical reconstruction of the 1642 AD flood. Through this reconstruction of the 1642 AD flood, a flood that resulted in the worst urban disaster in Yellow River history, reveals the series disaster spatial processes associated with the actual flood event. After introducing the disaster scene, this paper then goes on to help develop an understanding of the relationships between the geographical situation, climate factors, military purposes, people and the Yellow River at that time. The results show that reconstructing flood processes, is a very effective method for improving our understanding of major flood events, including natural and humanity effects of such events. Furthermore, the analysis of historical documents and archaeological findings may significantly contribute to a better and more detailed understanding of the space and time relationships involved in flood processes and the consequential impact of such floods.